IMPLEMENTATION OF THE TERRORISM FINANCING LAW IN COURT DECISIONS (Study of Decision No. 775/Pid.Sus/2015/PN. Jkt.Tim) - Gizandra Indah Gemici atakkerinci; Hendra Suherman; Deaf Wahyuni Ramadhani (AKADEMI TEKNIK ADI KARYA, 2023)
The eradicating criminal acts of terrorism is certainly not enough to use repressive measures alone, but there are also preventive efforts in it. The study aims to determine criminal law policies towards funding theorists in Indonesia. This research uses descriptive qualitative methods with a normative legal approach. The results showed that criminal law policies against terrorism financing have been implemented in Law Number 9 of 2013.The implementation of the Terrorism Financing Law in Court Decision Number 775/Pid.Sus/2015/PN.Jkt. is in accordance with regulations.